2011
DOI: 10.5897/sre11.618
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of chemically modified starches from different botanical origin

Abstract: Starches from various botanical origins (rice, maize and potato starches) were cross-linked in the presence of epichlorohydrin (EPI), respectively. Then, the cross-linked starches were further oxidized with sodium hypochlorite (NaOCl, 2.5% w/w) to obtain oxidized cross-linked starches (OCS). The chemically modified methods on the physicochemical properties of different starches were investigated. It was found that cross-linking treatment increased peak, setback and final viscosities of rice and maize starches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 28 publications
0
1
1
1
Order By: Relevance
“…A lower amylose content was observed after dual modification of yam starch when compared to crosslinking with STMP alone [29]. Huaxi et al [34] reported a DC of 20% in dual crosslinked potato starch which is lower than values observed in this present work. Higher values for DC (47.34% -58.28%) were reported after dual modification of lotus (Nelumbo nucifera) rhizome starch [35] while the dual modification of banana starch in another study had DC between 21.99% and 46.74% [36].…”
Section: Effect Of Dual Modification On Amylose Content Ds and DCcontrasting
confidence: 81%
“…A lower amylose content was observed after dual modification of yam starch when compared to crosslinking with STMP alone [29]. Huaxi et al [34] reported a DC of 20% in dual crosslinked potato starch which is lower than values observed in this present work. Higher values for DC (47.34% -58.28%) were reported after dual modification of lotus (Nelumbo nucifera) rhizome starch [35] while the dual modification of banana starch in another study had DC between 21.99% and 46.74% [36].…”
Section: Effect Of Dual Modification On Amylose Content Ds and DCcontrasting
confidence: 81%
“…Cv.GHB-223 and cv.GHB-732 showed non-significant (p < 0.05) difference in DC. Various workers have reported DC values ranging from 51.3% to 99.1% for corn starches, [8] 60.1% for potato, [25] 35.9% to 82.4% for cassava starch [5], and 7.17 to 87.29% for wheat starches. [10] Amylose content of cross-linked starches ranged from 6.2% to 8.5% (Table 1), the values observed were lower than those observed for their counterpart native starches.…”
Section: Resultsmentioning
confidence: 99%
“…Além da sua origem, a forma de extração do amido influência no seu uso e aplicabilidade industrial, além de interferir no seu comportamento reológico e nas propriedades físico-químicas e funcionais (Xiao et al, 2011;Correia et al, 2012;Correia et al, 2013). A proporção entre os dois principais componentes do amido, amilose e amilopectina, bem como o comprimento da cadeia são influenciadas pela fonte botânica e condições climáticas de estocagem do material de origem do amido, influenciando as características específicas da pasta e a funcionalidade do amido (Zhu et al, 2017).…”
Section: Introductionunclassified